Treatment Of Palm Oil Mill Effluent Odour Using Biofilter From Compost And Wood Chips Media - Nagalinggam, Tanagaraj (Universiti Sains Malaysia, 2017)
A biofilter is one of the system which are consists of micro-organisms populated container of organic material, through which will reduce the odour concentration flowing out from the system. The study was conducted to determine the suitable media or ratio of mixed media and operation condition for biofilter. The characteristic of wood chips and compost used for packing material in biofilter was conducted as it is one of the prime parameters for biofilter performance. The Palm Oil Mill effluent was tested to identify the odour removal efficiencies at varying biofilter operational conditions. The data collection is obtained from two biofilter which is in form of lab scale and it located at the laboratory. The sample gas of inlet and outlet from biofilter are collected for testing while data such as pH of filter media and pressure flow rate of gas sample inlet and outlet is taken directly at the biofilter at laboratory. United Oil Palm Industries Sdn.Bhd have been given permission to take palm oil effluent for research. Other than that, various test for the biofilter media samples was also conducted. Some of tests are conducted for the important parameter of biofilter performance which is characteristic test for media. The odour removal efficiency of all biofilters are obtained in different removal capacity. This conditions is occurred because can be affected by many parameters of biofilter performance. The Empty Bed Retention Time for all biofilter is same which 60s. Next, the pH for both biofilter media is optimum pH which through test pH value is reduce near to neutral pH is 6.5. The palm oil compost show better result in many physical parameters compared to wood chips. The odour removal efficiency results for compost is 96%. This research will help the engineers to determine the important parameters to consider for design and to open up new opportunity to introduce new type of filter media.